INVENTORY MANAGEMENT SYSTEMS ON SUPPLY CHAIN PERFORMANCE OF FAST-MOVING CONSUMER GOODS MANUFACTURERS IN KENYA - Muhalia, Eric Jepherson; Ngugi, Dr. Patrick Karanja; Moronge, Dr. Makori (International Journal of Supply Chain and Logistics, 2021)
Purpose: The purpose of this study was to determine the influence of inventory management systems on supply chain performance of fast-moving consumer goods manufacturers in Kenya Methodology: The study adopted descriptive research design. The unit of observation was the operations manager of the 51 FMCG manufacturers located in Nairobi. The sampling frame of the current study consisted of operations managers in the manufacturers of the FMCGs in Nairobi. The study used the census method to select 51 manufacturers of the FMCGs in Nairobi, thus the sample of the study was 51 respondents. Primary data was used in the study. The study used questionnaires to collect data. Mixed methods technique of analyzing data was used where both descriptive and inferential analysis were used. The data collected from the field was analyzed using SPSS 23 program. The questionnaires were referenced and the items in them coded for easier data entry. The presentation of the findings was done using tables. Results: The study found that inventory management systems positively and significantly influences Supply chain performance of FMCG in Kenya. The study found that respondents agreed that inventory management systems promotes improved supplier, vendor, and partner relationships; inventory management systems enables the company to maintain a centralized record of every asset; inventory management systems helps in reduction in storage costs; inventory management systems helps to keep track on current stock levels which enables the company to reorder with greater accuracy; and that inventory management systems promotes better reporting and forecasting capabilities. Unique contribution to theory, practice and policy: The study recommended that the recommends the company to adopt new technology (updated inventory management system) to ensure that the processes in the company are efficient; this can be achieved by upgrading operation standards and implementation of new technology and software. Because of technological itches, it is possible for the company to lose data, therefore it is recommended that the company should always have backup of inventory data.